Longitudinal analysis of alcohol use and intimate partner violence perpetration among men with HIV in northern Vietnam. (1st August 2020) - Hershow, Rebecca B.; Reyes, H. Luz McNaughton; Ha, Tran Viet; Chander, Geetanjali; Mai, Nguyen Vu Tuyet; Sripaipan, Teerada; Frangakis, Constantine; Dowdy, David W.; Latkin, Carl; Hutton, Heidi E.; Pettifor, Audrey; Maman, Suzanne; et al.
Highlights: Alcohol is associated with intimate partner violence among Vietnamese men with HIV. The strength of the alcohol-IPV relationship varies across drinking patterns. AUD and frequent drinking are stronger correlates of IPV than heavy drinking. Abstract: Background: Alcohol use is a known risk factor for male-perpetrated intimate partner violence (IPV), although few studies have been conducted globally and among men with HIV (MWH). We estimated the longitudinal effects of alcohol use on IPV perpetration among MWH. Methods: This study is a secondary analysis of randomized controlled trial data among male and female antiretroviral treatment patients with hazardous alcohol use in Thai Nguyen, Vietnam. Analyses were restricted to male participants who were married/cohabitating (N = 313). Alcohol use was assessed as proportion days alcohol abstinent, heavy drinking, and alcohol use disorder (AUD) using the Timeline Followback and Mini International Neuropsychiatric Interview questionnaire. Multilevel modeling was used to estimate the effects of higher versus lower average alcohol use on IPV perpetration (between-person effects) and the effects of time-specific deviations in alcohol use on IPV perpetration (within-person effects). Results: Participants with higher average proportion days alcohol abstinent had decreased odds of IPV perpetration (adjusted Odds Ratio [aOR] = 0.43, p = 0.03) and those with higher average heavy drinking and AUD had increased odds of IPV perpetration (Heavy drinking: aOR = 1.05, p = 0.002; AUD: aOR = 4.74, p < 0.0001). Time-specific increases in proportion days alcohol abstinent were associated with decreased odds of IPV perpetration (aOR = 0.39, p = 0.02) and time-specific increases in AUD were associated with increased odds of IPV perpetration (aOR = 2.95, p = 0.001). Within-person effects for heavy drinking were non-significant. Conclusions: Alcohol use is associated with IPV perpetration among Vietnamese men with HIV. In this context, AUD and frequent drinking are stronger correlates of IPV perpetration as compared to heavy drinking.